Goat semen cryopreservation using egg yolk and soya based extenders containing trehalose - NARWADE, B M; MOHANTY, TUSHAR KUMAR; BHAKAT, MUKESH; RAHIM, ABDUL (The Indian Journal of Animal Sciences, 2017)
To evaluate the effect of egg yolk and soybean based extenders containing trehalose on cryopreservation of goat spermatozoa. A total 100 ejaculates in winter were collected from 10 crossbred bucks. Ten pooled ejaculates from each buck were washed with phosphate buffer saline and splited into 4 different parts for dilution with 4 extenders (EXT): (EXT 1) tris (375mM), citrate (124mM), glucose (41mM) + 20% egg yolk (EY) (TCG); (EXT 2) TCG containing 131.25mM trehalose (TCG+T); (EXT 3) TCG + 25% soya and (EXT 4) TCG with 131.25mM trehalose + 25% soya. Analysis revealed that, the initial semen quality parameters except HOST did not differ significantly in all extenders. In soya based extender post-thaw live sperm and intact acrosome were significantly reduced than egg yolk based extender. Further, the addition of trehalose to both egg yolk and soya based extender significantly improved all the post- thaw semen quality parameters and superiority of post-thaw semen quality parameters were significantly observed in egg yolk based extender containing trehalose as compared to other semen extenders. It can be concluded that TGC containing 20% egg yolk and 35% as well as TCG containing 131.25mM trehalose are suitable for crossbred buck semen cryopreservation.